The Distribution Mapping for Environmental Evaluation of Waterlily (Nymphaea pubescens Willd.) Growing in Lebak Swampland in Kalimantan Selatan Province - Astinana Yuliarti; Bakti Nur Ismuhajaroh; Rosalina Kumalawati; Karnanto Hendra Murliawan; Rizky Nurita Anggraini; Asri Alkirani (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
The lotus is one of the aquatic plants that grow in the Lebak area and is widely used as food and medicine by the local community. The lotus growing environment determines its growth. The distribution of lotus plants has not been well identified. This study aims to determine the distribution of lotus mapping for environmental evaluation of lotus growing in Teluk Sinar Village, Sungai Pandan District, Hulu Sungai Utara Regency, South Kalimantan Province. The study used data collection methods with primary and secondary data survey techniques. Primary survey through delineation of lotus plant boundaries in the field. Field measurements were also carried out to identify the environmental variables of lotus growing. In addition, the interpretation of high-resolution satellite imagery and low-resolution satellite imagery for spectral analysis. The environmental variables for growing lotus include water depth, light penetration depth, water pH, and sediment pH. The results of the study revealed a map of the distribution of lotus and the growing environment of the lotus. The lotus distribution map was obtained from the results of overlaying several thematic maps, image interpretation, and field measurements using Arc View and Arc GIS software. The distribution of lotus plants can grow in an environment with a water depth of 35-121 cm, a light penetration depth of 23-100 cm, a water pH of 6.25-8.37, and a sediment pH of 3.33-4.69. The results of the Lotus Distribution Mapping and the Lotus growing environment obtained can be used as a basis for determining the potential distribution of Lotus in each region.